Utility of Mac‐2 Binding Protein Glycosylation Isomer to Evaluate Graft Status After Liver Transplantation. Issue 3 (1st October 2020) - Kimura, Yusuke; Taura, Kojiro; Hai Nam, Nguyen; Uemoto, Yusuke; Yoshino, Kenji; Ikeno, Yoshinobu; Okuda, Yukihiro; Nishio, Takahiro; Yamamoto, Gen; Tanabe, Kazutaka; Koyama, Yukinori; Anazawa, Takayuki; et al.
Abstract : Mac‐2 binding protein glycosylation isomer (M2BPGi) is a novel liver fibrosis biomarker, but there are few studies on M2BPGi in liver transplantation (LT) recipients. This study aimed to evaluate the utility of M2BPGi measurement in LT recipients. We collected the clinicopathological data of 233 patients who underwent a liver biopsy at Kyoto University Hospital after LT between August 2015 and June 2019. The median values of M2BPGi in patients with METAVIR fibrosis stages F0, F1, F2, and ≥F3 were 0.61, 0.76, 1.16, and 1.47, respectively, whereas those in patients with METAVIR necroinflammatory indexes A0, A1, and ≥A2 were 0.53, 1.145, and 2.24, respectively. Spearman rank correlation test suggested that the necroinflammatory index had a stronger correlation to the M2BPGi value than the fibrosis stage. The area under the receiver operating characteristic curve of M2BPGi to predict ≥A1 was 0.75, which was significantly higher than that of any other liver fibrosis and inflammation marker. Patients with a rejection activity index (RAI) of ≥3 had a higher M2BPGi value than those with RAI ≤ 2 ( P  = 0.001). Patients with hepatitis C virus viremia had a higher M2BPGi value than sustained virological responders or those with other etiologies. In conclusion, the present study demonstrated that M2BPGi values are more strongly influenced by necroinflammatory activity and revealed M2BPGi, which has been thought to be a so‐called fibrosis marker, as a disease activity marker in transplant recipients. M2BPGi measurement may be useful to detect early stage liver inflammation that cannot be detected by routine blood examination of LT recipients.